Child and Adolescent Depression: A Review of Theories, Evaluation Instruments, Prevention Programs, and Treatments - Bernaras, Elena; Jaureguizar, Joana; Garaigordobil, Maite (Frontiers in Psychology, 2019)
Depression is the principal cause of illness and disability in the world. Studies charting the prevalence of depression among children and adolescents report high percentages of youngsters in both groups with depressive symptoms. This review analyzes the construct and explanatory theories of depression and offers a succinct overview of the main evaluation instruments used to measure this disorder in children and adolescents, as well as the prevention programs developed for the school environment and the different types of clinical treatment provided. The analysis reveals that in mental classifications, the child depression construct is no different from the adult one, and that multiple explanatory theories must be taken into account in order to arrive at a full understanding of depression. Consequently, both treatment and prevention should also be multifactorial in nature. Although universal programs may be more appropriate due to their broad scope of application, the results are inconclusive and fail to demonstrate any solid long-term efficacy. In conclusion, we can state that: (1) There are biological factors (such as tryptophan—a building block for serotonin-depletion, for example) which strongly influence the appearance of depressive disorders; (2) Currently, negative interpersonal relations and relations with one's environment, coupled with social-cultural changes, may explain the increase observed in the prevalence of depression; (3) Many instruments can be used to evaluate depression, but it is necessary to continue to adapt tests for diagnosing the condition at an early age; (4) Prevention programs should be developed for and implemented at an early age; and (5) The majority of treatments are becoming increasingly rigorous and effective. Given that initial manifestations of depression may occur from a very early age, further and more in-depth research is required into the biological, psychological and social factors that, in an interrelated manner, may explain the appearance, development and treatment of depression.